1993
DOI: 10.1002/mrd.1080340111
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic studies of the plasma membrane block to polyspermy in mouse eggs

Abstract: The mechanisms responsible for the plasma membrane associated block to polyspermy in mouse eggs were studied. Reinsemination experiments using zona-free eggs indicated that, after fertilization, the egg plasma membrane is altered such that sperm binding to the egg plasma membrane is blocked, except in the region of the second polar body. Activation of the egg with either ethanol or strontium chloride did not result in a block to polyspermic penetration, as artificially activated eggs displayed identical penetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
3

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 41 publications
6
68
3
Order By: Relevance
“…35 Plasma membrane block is assumed to result from changes (eg, the destruction of sperm receptors in the membrane) that preclude sperm adherence. 36,37 Recent studies have demonstrated that the UPS is responsible for extracellular degradation of the sperm receptor on the outer face of zona pellucida and that proteasomal inhibitors block sperm penetration of the zona pellucida during fertilization. [17][18][19] These findings strongly support a role for the UPS in the sperm-oocyte interaction of the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…35 Plasma membrane block is assumed to result from changes (eg, the destruction of sperm receptors in the membrane) that preclude sperm adherence. 36,37 Recent studies have demonstrated that the UPS is responsible for extracellular degradation of the sperm receptor on the outer face of zona pellucida and that proteasomal inhibitors block sperm penetration of the zona pellucida during fertilization. [17][18][19] These findings strongly support a role for the UPS in the sperm-oocyte interaction of the zona pellucida.…”
Section: Discussionmentioning
confidence: 99%
“…These conditions were optimized to generate monospermic eggs since polyspermic eggs show a higher frequency of Ca 2C transients (Faure et al 1999) and this altered Ca 2C signaling could potentially affect egg activation events, including the membrane block to polyspermy. Eggs were cultured for 3 h following activation by treatment with A23187 or by fertilization, as previous data suggest the membrane block is established in 0.75-2 h post-insemination (Wolf 1978, Horvath et al 1993, Sengoku et al 1995, Redkar & Olds-Clarke 1999, McAvey et al 2002. Previous work had allowed 40 min after ionophore treatment before challenging the eggs with sperm (Wolf et al 1979).…”
Section: Camentioning
confidence: 99%
“…This observation raised the question of whether a single increase in [Ca 2C ] cyt was sufficient to establish a partially effective membrane block to polyspermy, and prompted us to examine the effects of parthenogenetic activation with the Ca 2C ionophore A23187, which induces a single increase in [Ca 2C ] cyt , on membrane block establishment. While it has been reported previously that parthenogenetically activated eggs did not establish a membrane block to polyspermy, our analyses here included some important variables not included in previous studies (Wolf et al 1979, Horvath et al 1993). First, we tested the hypothesis that post-ovulatory time could affect the ability of eggs to establish a membrane block to polyspermy in response to treatment with Ca 2C ionophore, as aged eggs are more responsive to parthenogenetic stimuli (Fulton & Whittingham 1978, Nagai 1987, Collas et al 1989, Ware et al 1989, Fissore & Robl 1992, Abbott et al 1998.…”
Section: Effects Of Calcium Ionophore-induced [Ca 2c ] Cyt Increase Omentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, the role of the CG exudate in establishing a plasma membrane block to polyspermy has been controversial. Whereas Wolf and Hamada (1977) originally supported a role for a CG proteinase in this block, subsequent studies on mice suggest that CG components do not participate in the plasma membrane block (Wolf et al, 1979;Horvath et al, 1993). However, in these latter experiments, ZP-free oocytes were used, and CG materials could have diffused away from the plasma membrane before setting up a block to polyspermy.…”
Section: Heparin Binding Placental Protein (Hbpp)mentioning
confidence: 99%